A dynamic allocation mechanism for formulating the allocation schemes of water resources - Jie Hou; Ni Wang; Jungang Luo; Ganggang Zuo; Liu Yang; Jiancang Xie (Water Supply, 2023)
Scientific and effective water allocation schemes are crucial for managing water resources. Traditional allocation schemes are built on an annual basis and fixed. However, because of the drastic spatio-temporal fluctuations in the availability and demand of water resources, fixed annual allocation schemes are impracticable. This work proposed a dynamic allocation mechanism that can divide annual allocation schemes into monthly scales and dynamically correct allocation schemes to make them adapt to the above fluctuations. First, a total quantity allocation model, which focuses on fairness and efficiency, was developed to allocate annual water resources. Secondly, a combination weighting model for a monthly water allocation was built using game theory to make the allocation schemes stricter and more executable. Thirdly, a dynamic allocation mechanism was constructed to dynamically correct the allocation schemes. The results indicate that (1) coupling a total quantity allocation scheme with monthly allocation schemes is more in line with management requirements and (2) compared with static allocation schemes, rolling correction schemes can reduce the deviation between planned and actual water consumption by 10–20%. A dynamic allocation mechanism can make water resource allocation schemes more resilient to spatiotemporal changes in supply and demand of water resources. HIGHLIGHTS Coupling the annual total quantity allocation model and the monthly allocation model to formulate allocation schemes is better for achieving strict water resource management.; The dynamic rolling correction mechanism can significantly reduce the deviation between the planned and actual water consumption.;